THE EFFECT OF EDUCATIONAL VIDEOS ON THE LEVEL OF KNOWLEDGE AND PERSONAL SAFETY SKILLS IN PREVENTING CHILD SEXUAL VIOLENCE SDN KEBON BESAR 2 TANGERANG CITY - Riski Nurhayati; Ema Hikmah; Osep Yasier Almunsiri (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Child sexual abuse is sexual coercion or exploitation that is inappropriate for the child's age or emotional condition, including various sexual acts. In 2023, there were 10,932 cases of child sexual abuse in Indonesia. The high rate of sexual abuse is due to a lack of information about sexuality, which is considered taboo. Objective: The objective of this study is to determine whether educational videos have an effect on the level of knowledge and personal safety skills in preventing child sexual abuse at SDN Kebon Besar 2 Elementary School in Tangerang City. Method: This study used a quantitative method with a quasi-experimental research design and a two-group design. The study population consisted of 70 respondents, with a sample size of 45 people. Bivariate analysis in this study used a bivariate test using a t-test. Results: The results of the study showed that the level of knowledge in the intervention group increased by 9.78 with a p-value of 0.000 (α 0.05), and personal safety skills in the intervention group increased by 24.00 with a p-value of 0.266 (α 0.05). Conclusion: Educational videos significantly affected knowledge of preventing child sexual violence, but not personal safety skills.